2020
DOI: 10.1038/s41401-020-0389-3
|View full text |Cite
|
Sign up to set email alerts
|

Alflutinib (AST2818), primarily metabolized by CYP3A4, is a potent CYP3A4 inducer

Abstract: Alflutinib (AST2818) is a third-generation epidermal growth factor receptor (EGFR) inhibitor that inhibits both EGFR-sensitive mutations and T790M mutations. Previous study has shown that after multiple dosages, alflutinib exhibits nonlinear pharmacokinetics and displays a time- and dose-dependent increase in the apparent clearance, probably due to its self-induction of cytochrome P450 (CYP) enzyme. In this study, we investigated the CYP isozymes involved in the metabolism of alflutinib and evaluated the enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…AST5902 is the major metabolite of alflutinib (52%) and can also be induced by CYP3A4. 27 A phase 2 trial of alflutinib (ALSC003) enrolled a total of 220 centrally confirmed Chinese patients with EGFR T790Mþ NSCLC, among whom 39.5% had brain metastasis by IRC. At the time of the data cutoff (January 2020), the IRC-ORR was 74.1% (95% CI: 67.8-79.7) (163 of 220) (Fig.…”
Section: Almonertinib (Hs-10296)mentioning
confidence: 99%
“…AST5902 is the major metabolite of alflutinib (52%) and can also be induced by CYP3A4. 27 A phase 2 trial of alflutinib (ALSC003) enrolled a total of 220 centrally confirmed Chinese patients with EGFR T790Mþ NSCLC, among whom 39.5% had brain metastasis by IRC. At the time of the data cutoff (January 2020), the IRC-ORR was 74.1% (95% CI: 67.8-79.7) (163 of 220) (Fig.…”
Section: Almonertinib (Hs-10296)mentioning
confidence: 99%
“…A correlation between the plasma concentration of some TKIs and the occurrence of drug-related AEs and resistance to therapy was described by Yu et al [ 16 ]. Plasma concentrations of osimertinib, aumolertinib, and furmonertinib can be affected by various factors such as pathophysiology, genetic polymorphisms, patient adherence to therapy, and interacting medications [ 17 , 18 , 19 , 20 ], leading to large inter-patient variability in efficacy and AEs. Therefore, it is necessary to monitor disease response and plasma drug concentrations to improve patient outcomes [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variability of the well-known pharmacogenes alleles could explain only part of the inter-individual differences in drug responses, and rare genetic variants in pharmacogenes such as SLC30A8 could modulate antidepressant (desipramine or fluoxetine) treatment 17 . The potential role on the disease development and drug efficacy of the rare variants in these genetically polymorphic pharmacogenes would be interesting and needed to be studied further 18 , 19 . The present study demonstrated that 91.1% of the 617 deleterious missense variants in the 125 pharmacogenes were rare (Fig.…”
Section: Discussionmentioning
confidence: 99%